Towards the construction of representative regional hydro(geo)logical numerical models: Modelling the upper Danube basin as a starting point - Pujades, Estanislao; Kumar, Rohini; Houben, Timo; Jing, Miao; Rakovec, Oldrich; Kalbacher, Thomas; Attinger, Sabine (Frontiers in Earth Science, 2023)
Introduction: Pressure on groundwater resources is increasing rapidly by population growth and climate change effects. Thus, it is urgent to quantify their availability and determine their dynamics at a global scale to assess the impacts of climate change or anthropogenically induced pressure, and to support water management strategies. In this context, regional hydrogeological numerical models become essential to simulate the behavior of groundwater resources. However, the construction of global hydrogeological models faces a lot of challenges that affect their accuracy. Methods: In this work, using the German portion of the Upper Danube Basin (∼43,000 km2) we outline common challenges encountered in parameterizing a regional-scale groundwater model, and provide an innovative approach to efficiently tackle such challenges. The hydrogeological model of the Danube consists of the groundwater finite element code OpenGeoSys forced by the groundwater recharge of the surface hydrological model mHM. Results: The main novelties of the suggested approach are 1) the use of spectral analyses of the river baseflow and a steady state calibration taking as reference the topography to constraint the hydraulic parameters and facilitate the calibration process, and 2) the calibration of the hydraulic parameters for a transient state model by considering parameters derived from the piezometric head evolution. Discussion/conclusion: The results show that the proposed methodology is useful to build a reliable large-scale groundwater model. Finally, the suggested approach is compared with the standard one used by other authors for the construction of global models. The comparison shows that the proposed approach allows for obtaining more reliable results, especially in mountainous areas.